Toxicological screening of traditional medicine Laghupatha (Cissampelos pareira) in experimental animals - Amresh G.; Singh P.N.; Rao C.V. (My University, 2025)
Laghupatha (Cissampelos pareira) a important medicinal plant in Indian traditional system of medicine and is widely used in many countries by different tribal. Despite the wide use of Cissampelos pareira in folk medicine, no study has been published in the scientific literature about its toxicological profile. In present study 50% aqueous ethanolic extract of Cissampelos pareira (Menispermaceae) was evaluated for the acute and subacute toxicity. In the acute toxicity test, oral administration of 2 g/kg of Cissampelos pareira produced neither mortality nor changes in behavior or any other physiological activities in mice. In subacute toxicity studies, no mortality was observed when the two doses of 1 or 2 g/kg day of 50% aqueous ethanolic extract of Cissampelos pareira were administered p.o. for a period of 28 days in rats. There were no significant changes occurred in the blood chemistry analysis including glucose, sodium, potassium, calcium, phosphorus, chloride, total cholesterol, high density lipoprotein, triglycerides, total protein, blood urea nitrogen, creatinine, conjugated billirrubin, aspartate transaminase, alanine transaminase, total billirrubin, albumin, prothrombin time and thromboplastin partial time in both sexes of animals. Hematological analysis showed no marked differences in any of the parameters examined (WBC count, platelet and hemoglobin estimation) in either the control or treated group of both sexes. The urinalysis was negative for glucose, ketonic bodies, casts, red blood cells, and albumin in the control and treatment groups. There were no significant differences in the body and organ weights between controls and treated animals of both sexes. Pathologically, neither gross abnormalities nor histopathological changes were observed. Cissampelos pareira was found safe in acute and subacute toxicities while chronic toxicity studies are further required for the support of the safe and sound use of this traditional plant. © 2007 Elsevier Ireland Ltd. All rights reserved.